A két világháború közötti magyar–olasz kapcsolatok vázlata = The aspects of the Hungarian-Italian relations in the interwar period - Hamerli, Petra (Közép-Európai Közlemények, 2017)
In my paper I would like to present the most signifi cant aspects of the Hungarian–Italian relations in the Interwar Period, which is my main research topic. The two States’ political interests met after World War I, but in the fi rst years (1918–1927) they both were cautious, and oscillated between the approach to each other and to the Little Entente States. After signing the Treaty of Friendship on 5 April 1927, the Hungarian–Italian cultural, political and economic relations were blooming. The fi rst step – which can be considered as a vehicle of the diplomatic relations – was the strenghtening of their cultural ones, of which most important result was the foundation of the Hungarian Academy in Rome. The Italian–Hungarian diplomatic collaboration was concentrating mainly on the common suport of the separatists in Yugoslavia (Ustasha Movement, Internal Macedonian Revolutionary Organization) to move the disintegration, or, at least, the weakening of the South-Slavic State, and on the Hungarian Treaty Revision, which was supported by Italy. These aspirations could become partly successful just from the end of the 1930s, when Germany also took part in their realization. Regarding the economic relations, bilateral agreements were made which cannot be considered to be really signifi cant. From 1934 to 1938, by the Roman Protocols signed on 17 March 1934, a trilateral collaboration began, as Austria joined to Hungary and Italy, which made the economic relations to be a bit successful. From 1936 the German infl uence increased in Central-Europe, and after the Anschluss in 1938 it became a determining factor in the formation of the Italian–Hungarian relations, too.